Molecular dynamics simulation of deformation accumulation in repeated nanometric cutting on single-crystal copper. Issue 17 (27th February 2015) - Zhang, Lin; Zhao, Hongwei; Dai, Lu; Yang, Yihan; Du, Xiancheng; Tang, Pengyi; Zhang, Li
<x xml:space="preserve">Abstract</x> The machining-induced residual defects and stress in subsurfaces determine the mechanical properties of the finished surfaces of bulk materials.